Temperature‐ and Atmosphere‐Dependent Defect Chemistry Model of SnO2 Nanocrystalline Film. Issue 7 (1st April 2014) - Zhang, Guozhu; Xie, Changsheng; Zhang, Shunping; Yang, Li; Xiong, Ya; Zeng, Dawen; Stevenson, J.
<x xml:space="preserve">Abstract</x> By combining the concept of defect chemistry and the small‐polaron hopping conduction model, the present work takes an intensively considering of the electron conduction mechanism in the nonstoichiometric SnO2 nanocrystalline film. The temperature‐dependent and atmosphere‐dependent relationship between the electrical conductivity and the defect reaction is outlined. To investigate the influence of temperature and atmosphere on the electrical properties of the SnO2 nanocrystalline film, a temperature‐programmed system integrated with the high‐throughput screening platform of gas‐sensing materials (HTSP‐GM) is developed as the test tool in this work. With this platform, the temperature‐dependent conductivity of SnO2 nanocrystalline film in different atmosphere (dry air, nitrogen, and formaldehyde) was conducted. A good fit between the theoretical deductions and experimental results is achieved.